Switching between intramolecular charge transfer and excimer emissions in solids based on aryl-modified ethynyl‒o-carboranes - Hideki Yamamoto; Junki Ochi; Kazuhiro Yuhara; Kazuo Tanaka; Yoshiki Chujo (Cell Reports Physical Science, 2022)
Summary: Because of its unique electronic properties, o-carborane has attracted attention as a scaffold for constructing solid-state luminescent materials. Here, we report stimulus-responsive luminochromic materials based on polycyclic aromatic hydrocarbon (PAH), such as anthracene and pyrene, modified with the ethynyl-o-carborane unit. Initially, luminochromism originating from switching of different emission mechanisms is described between intramolecular charge transfer (ICT) emission and excimer emission triggered by mechanical stimuli, heat, and vapor annealing regarding the single o-carborane-substituted anthracene. Next, the luminescence properties of two ethynyl-o-carboranes at both ends of PAHs are presented. In particular, multi-step mechanochromic luminescence of the pyrene derivative is explained. Stepwisely changes triggered by weak stimuli that can induce cracking sites, followed by luminochromic behavior and by grinding treatment, which causes phase transition from crystal to amorphous, leading to luminescent mechanism changes from ICT emission to excimer emission.